Strategi Kompensasi Dan Tunjangan Berbasis Fleksibilitas Dalam Meningkatkan Retensi Karyawan Generasi Z Pada Era Transformasi Digital - Marsya Callista Putri; Saskia Aurelia; Aura Fathinah; Muhammad Miftah Giffari; Vanesya Dwi Naiya; Chintya Ones Charli (GLOBAL SCIENTS PUBLISHER, 2026)
The development of the workforce in the digital era is currently marked by the entry of Generation Z as a new workforce. Generation Z has characteristics such as being skilled in using technology, active, and highly concerned about comfort and well-being in the workplace. The main problem faced by companies today is the high rate of employee turnover or the habit of frequently changing jobs among this generation. This study aims to find out how compensation and benefit strategies that are not rigid and can adjust to employee needs can increase loyalty and retain Generation Z employees in the company. The research method used is descriptive qualitative with a literature review approach, where data are collected from previous journals and human resource management reports. The results show that old compensation systems that are rigid and the same for everyone are no longer effective in retaining Generation Z, so companies need to give employees the freedom to choose benefits that suit their needs, such as mental health support, internet cost assistance for working from home, and digital training support. This study is expected to help companies create a reward system that is easier to adjust to employee needs.